Pharmacological effects of Cnicus arvensis on the gastrointestinal system - Fatima Saqib; Sakeena Hassan; Imran Imran; Ambreen Aleem; Khalid Hussain Janbaz (Bangladesh Pharmacological Society, 2018)
The current study was conducted to screen the possible pharmacological activity of Cnicus arvensis on the gastrointestinal system. The methanolic extract exerted concentration-dependent (0.01-3.0 mg/mL) spasmolytic effect using isolated tissue preparations of rabbit jejunum and caused relaxation of K+(80 mM)-induced spastic contractions. There was non-parallel shift in Ca++ concentration response curves towards right at tissue bath concentrations of 0.3 and 1.0 mg/mL. The solvent-solvents fractionation revealed domination of spasmolytic effects in petroleum ether fraction as compared to aqueous fraction. The methanolic extract also found to reduce the retching in chicks at 150 mg/kg as compared to chlorpromazine. The methanolic crude extract also found to reduce the number of wet spots using castor oil-induced diarrhea in rat as compare to loperamide. Our results reflected the presence of Ca++ channel blocking activity in methanolic extract, thus rationalizing the medicinal use of C. arvensis in diarrhea and vomiting.